PENANAMAN NILAI-NILAI PENDIDIKAN KARAKTER PESERTA DIDIKDI LINGKUNGAN SEKOLAH DASAR - Amin, Muhammad; Pulungan, Samsuddin; Hamidah, Hamidah (Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Padangsidimpuan, 2025)
Character education is very important in building human resources (HR), because good and bad characters are closely related to a person's education. All parties (family, society, and government) must realize that character emerges from the world of education. Therefore, character education must begin early, namely elementary school (SD) and middle school (SMP). In character education, strategies and materials are needed that must be taught to students. From the strategy, it is hoped that students can easily absorb the material, and the character material learned can be applied in their daily lives. This study aims to describe the actual concept related to the instillation of character education values among students. This study uses descriptive qualitative research methods and types, data obtained from books and articles are systematically analyzed according to the topics of discussion. Then presented, conclusions are made and verified. Primary and secondary data are described according to the formulated systematics, so that the problems discussed can be understood into a complete concept. The strategies for instilling character education values for elementary and middle school students are: Incorporating character education into all subjects at school, Creating slogans or cheers that can foster habits for all school communities to behave well, getting used to positive behavior among school residents, and conducting continuous monitoring, giving prizes to students who always have good character. The character education values that must be instilled for elementary and middle school students are Religious, Honest, Tolerant, Disciplined, Hard Work, Creative, Independent, Democratic, Curiosity, National Spirit, Love for the Country, Appreciating Achievement, Friendly/Communicative, Love Peace, Love Reading, Care for the Environment, Care for Social and Responsible